Mesoporous molybdenum carbide for greatly enhanced hydrogen evolution at high current density and its mechanism studies - Juan Li; Chun Tang; Heng Zhang; Zhuo Zou; Chang Ming Li (Materials Reports: Energy, 2023)
Currently the catalysis of hydrogen evolution reaction (HER) is mainly focused on the inherent electrocatalytic activity at relatively lower current densities while scarce at high current densities. Nevertheless, the latter is highly demanding in efficient mass-production of hydrogen. A SiO2 nanospheres template-synthesis is used to prepare mesoporous molybdenum carbide nanocrystals-embedded nitrogen-doped carbon foams (mp-Mo2C/NC). The material shows much more excellent catalytic activity than the non-etched Mo2C/NC toward hydrogen evolution reaction (HER) in acidic medium. More interestingly mp-Mo2C/NC still has larger overpotential than Pt/C at lower current densities, but possess remarkably smaller overpotential than the latter at higher current densities for much better electrocatalytic performance. An approach is developed to investigate the electrode kinetics by Tafel plots, especially with eliminating the diffusion effect, indicating that Pt/C and mp-Mo2C/NC display different reaction mechanisms. At low current densities the former presents reversible reaction, while the latter shows mixed electrochemical polarization/reversible electrode process. In the region of higher current densities, the former becomes totally gas-diffusion controlled with large overpotential, while the latter can still retain an electrode polarization process for much lower overpotential at the same current density. Result endorses that the meso-porously structured mp-Mo2C/NC plays a critical role in avoiding gas diffusion control-resulting large overpotential at high current densities. This work holds great potential for an inexpensive catalyst better than Pt/C in practical applications of mass-production hydrogen at high current densities, while clearly shedding fundamental lights on designs of rational HER catalysts for the uses at high current densities.